Comportamento de presentear e estratégias reprodutivas - Souza, Diego Fernandes (2014)
Gift giving is a universal behavior, occurring between friends, family, romantic partners and even between strangers. Among several situations, we chose to investigate gift giving in the context of romantic partnership. Most evolutionary studies have related gift giving with the courting phase, given the comparison with other animals that also exhibit the gift giving behavior. However, the literature provides data to support the hypothesis that such behavior would receive greater investment when used for maintaining relationships and partnerships for long-term. The first paper investigated what situation (search vs retention) and type of partnership (short vs long-term) receives more investment as well as similarities and differences between the sexes. Furthermore, we investigated the influence of family unpredictability in childhood in the use of reproductive strategies and their influence on gift giving. The second paper, in turn, investigated similarities and differences between men and women in motivations for gift giving romantic partners and how these can be influenced by reproductive strategies partners. The results, in general, indicate that gift giving might have been selected in order to maintain the romantic relationship. In addition, the study showed an instrument that contemplates a new perspective related to motivation for gifting romantic partners, expanding the number of instruments with evolutionary basis and also the possibilities to identify relationships between the constructs presented here and others consolidated in the area.